2022
DOI: 10.1073/pnas.2200652119
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of COVID-19 testing and contact tracing in a US city

Abstract: Although testing, contact tracing, and case isolation programs can mitigate COVID-19 transmission and allow the relaxation of social distancing measures, few countries worldwide have succeeded in scaling such efforts to levels that suppress spread. The efficacy of test-trace-isolate likely depends on the speed and extent of follow-up and the prevalence of SARS-CoV-2 in the community. Here, we use a granular model of COVID-19 transmission to estimate the public health impacts of test-trace-isolate programs acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The study shows that within the prevention strategies subgroup of the school-associated risk factors, contact tracing initiated by the school and testing policy contributed the most to the total impact score among both age groups. This finding is consistent with previous studies [ 12 , 13 ], which indicated that contact tracing programs and testing policies can be highly effective in swiftly preventing infections on campuses and in the community. As one of the earliest applied preventive strategies, the requirement for facial covering was another contributor to the impact score.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study shows that within the prevention strategies subgroup of the school-associated risk factors, contact tracing initiated by the school and testing policy contributed the most to the total impact score among both age groups. This finding is consistent with previous studies [ 12 , 13 ], which indicated that contact tracing programs and testing policies can be highly effective in swiftly preventing infections on campuses and in the community. As one of the earliest applied preventive strategies, the requirement for facial covering was another contributor to the impact score.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to preventive behaviours, increased testing is essential to prevent the spread of the disease in society. This approach can improve case detection, isolation of infected individuals, and contact tracing [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, contacts may not follow recommendations, for instance they may evade quarantine or not use protective measures such as masks. Second, for manual contact tracing, the delay in notification and the number of contacts identified (13) may limit its effectiveness, since each new contact requires a minimum amount of time to be reached (14) and not all contacts can be reached in time to apply effective measures against the spread of SARS-CoV-2. Third, there could be intentional or un-intentional under-reporting.…”
Section: Introductionmentioning
confidence: 99%
“…9 Contact tracing, which requires keeping track of those with whom diagnosed patients have had close contact, has been recognized as an effective mitigation policy. 10,11 However, the limitations of its contact-detecting ability and the low uptake of apps shook the reliability of the effectiveness to its foundations. .…”
Section: Introductionmentioning
confidence: 99%